Unstructured kinetic model for batch fermentation of USP glycerol for lactic acid production - López Giraldo, Luis Javier; Gamboa Rueda, Jimy Alexander; Lizcano González, Víctor Alexis; Ordoñez Supelano, Mario Andrés; Pérez Mendoza, José Andrés; Guzmán Luna, Carolina (CT&F - Ciencia, Tecnología y Futuro, 2015)
This study show the capability of Lactobacillus rhamnosus ATCC 7469 to produce lactic acid using crude glycerol from biodiesel production as carbon source; in addition, a kinetic model that describes the behaviour of the fermentation process using USP glycerol as substrate was proposed and developed. The strain was adapted to the new carbon source by doing successive cultures, the substrate conversion was up to 94.5% after 24 hours of fermentation using crude glycerol as under initial conditions of substrate concentration (crude glycerol) and pH of 8 g/L and 6.5, respectively. Then, the influence of initial pH (pHo) and concentration of substrate (So) were evaluated by fermentation tests of USP glycerol. The optimal value of volumetric lactic acid productivity (Qv) achieved from this study was 0.087 g.L-1.h-1 for initial pHo = 6.5 and initial substrate concentration So = 6 g/L. Lastly, the kinetics parameters of an unstructured and not segregated model (Aiba type equation for growth rate expression), were adjusted with an average fit degree of 88% for all the initial conditions, using USP glycerol. In addition, the kinetic parameters are laid out as function of initial pH and substrate concentration.